2015
DOI: 10.1371/journal.pone.0140609
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis in Haematococcus pluvialis: Astaxanthin Induction by Salicylic Acid (SA) and Jasmonic Acid (JA)

Abstract: Haematococcus pluvialis is an astaxanthin-rich microalga that can increase its astaxanthin production by salicylic acid (SA) or jasmonic acid (JA) induction. The genetic transcriptome details of astaxanthin biosynthesis were analyzed by exposing the algal cells to 25 mg/L of SA and JA for 1, 6 and 24 hours, plus to the control (no stress). Based on the RNA-seq analysis, 56,077 unigenes (51.7%) were identified with functions in response to the hormone stress. The top five identified subcategories were cell, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 37 publications
4
50
0
Order By: Relevance
“…A possible explanation would be that excessive GGPPS might inhibit the astaxanthin biosynthesis in E. coli. This hypothesis is partly supported by the evidence that no change or downregulation of GGPPS was found in the salicylic acid and jasmonic acid stressed transcriptome analysis in H. pluvialis during astaxanthin formation [39]. Further research can be conducted to test the suppressive role of GGPPS during astaxanthin biosynthesis.…”
Section: Discussionmentioning
confidence: 82%
“…A possible explanation would be that excessive GGPPS might inhibit the astaxanthin biosynthesis in E. coli. This hypothesis is partly supported by the evidence that no change or downregulation of GGPPS was found in the salicylic acid and jasmonic acid stressed transcriptome analysis in H. pluvialis during astaxanthin formation [39]. Further research can be conducted to test the suppressive role of GGPPS during astaxanthin biosynthesis.…”
Section: Discussionmentioning
confidence: 82%
“…The astaxanthin synthetic pathway has been studied in some higher plants and microalgae (20)(21)(22). However, little is known regarding the pathway of Schizochytrium's astaxanthin biosynthesis.…”
mentioning
confidence: 99%
“…PSY is regarded as a rate‐determining key enzyme or an important control point for regulation of carbon fluxes toward the carotene biosynthetic pathway, which catalyzes the first committed step of this pathway and converts two geranylgeranyl pyrophosphate (GGPP) to phytoene (Cordero et al, ; RodrĂ­guez‐VillalĂłn et al, ). CHYb, catalyzing β‐carotene hydroxylation, is also an important enzyme in the astaxanthin biosynthesis pathway (Gao et al, ). The accumulation of astaxanthin is always accompanied by significant upregulation of CHYb and BKT (β‐carotene ketolase gene) in H. pluvialis (Gao et al, ; Gwak et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…CHYb, catalyzing β‐carotene hydroxylation, is also an important enzyme in the astaxanthin biosynthesis pathway (Gao et al, ). The accumulation of astaxanthin is always accompanied by significant upregulation of CHYb and BKT (β‐carotene ketolase gene) in H. pluvialis (Gao et al, ; Gwak et al, ). Huang et al () also found that BKT was upregulated in transcriptional expressions under mixotrophic conditions.…”
Section: Resultsmentioning
confidence: 99%